JUSTIFICATION OF TRANSITION FROM ZONING OF CONTAMINATED TERRITORIES TO SETTLEMENTS CLASSIFICATION AT AN AVERAGE ANNUAL EFFECTIVE DOSES IN REMOTE PERIOD AFTER THE CHERNOBYL NPP ACCIDENT - N. G. Vlasova; Y. V. Visenberg; A. N. Mataras (Радиационная гигиена)
In an existing exposure situation (in a remote period after the Chernobyl accident) there is a need of the transition from "radioactive area zoning" to "the settlements classification by average annual effective doses to the critical group of persons among the settlement's residents", to ensure the appropriate radiation level and social protection of the settlement's residents, located on the contaminated territory.The comparative allocation analysis of the average annual external and internal effective doses, the average annual effective cumulative doses to residents of settlements, related to the relevant areas (the Council of Ministers of Belarus latest decision, the proposed dose range according to the Catalogue of average annual effective doses of residents of settlements radiation Republic of Belarus) confirmed the validity of the transition from "radioactive zoning area" to "the classification of settlements by average annual effective dose."In accordance with the radiation protection principles, it seems reasonable to classify the settlements located on the contaminated territory at the average annual effective dose as follows: < 0.1 mSv / year (not required to carry out radiation protection measures in the agricultural sector);  0.1-1 mSv / year (periodic radiation monitoring should be carried out);  1 mSv / year (it is necessary to apply a complex of protective measures).